The legal support of the migration in China - Boldurukova, N B; Dauyen, D B (Journal of Oriental Studies, 2016)
The article research the legal regulation of migration processes in China. Overseas Chinese community is the largest on the World. China has established a system of regulation of relations with Chinese migrants. There was established a good legal framework in China for effective and useful relation with huaqiao. One of the case of development of China was the investments of this huaqiao.